2007
DOI: 10.1007/s12034-007-0097-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silica nanosphere from homogeneous and heterogeneous systems

Abstract: Silica nanosphere was synthesized using homogeneous and heterogeneous systems, respectively. In homogeneous system, silica spheres were synthesized without cetyltrimethylammonium bromide (CTABr), which gave bimodal particle size and lower yield (77%). To improve the yield, CTABr was added and found that the yield was very high (100%). The particle was in nm range, but the particle sizes are bimodal. To avoid it, reaction in heterogeneous system using CTABr was carried out. Nanosized silica sphere with uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 9 publications
(9 reference statements)
0
17
0
2
Order By: Relevance
“…20 Recently, silica nanoparticles (SiO 2 ) have become popular materials with potential applications in numerous elds, including ceramics, catalysts, pharmaceutical products, electronic packaging, photonic and chemical-mechanical polishing due to their ordered mesostructure, large surface area, exible pore size, and thermal stability. [21][22][23] Due to such advantages, silica nanoparticles (SiO 2 ) have been considered to have be photocatalyst with higher efficiency than TiO 2 . 20,24,25 In addition, the improvement in the pore diameter, pore volume and surface area of the silica nanoparticles has attracted a signicant amount of attention in various elds of science.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recently, silica nanoparticles (SiO 2 ) have become popular materials with potential applications in numerous elds, including ceramics, catalysts, pharmaceutical products, electronic packaging, photonic and chemical-mechanical polishing due to their ordered mesostructure, large surface area, exible pore size, and thermal stability. [21][22][23] Due to such advantages, silica nanoparticles (SiO 2 ) have been considered to have be photocatalyst with higher efficiency than TiO 2 . 20,24,25 In addition, the improvement in the pore diameter, pore volume and surface area of the silica nanoparticles has attracted a signicant amount of attention in various elds of science.…”
Section: Introductionmentioning
confidence: 99%
“…Polydimetylsiloxan là một polyme silic hữu cơ, với cấu tạo được hình thành từ các monome (CH 3 ) 3 SiOH. Quá trình chức hóa chính là quá trình phân tán polydimetylsiloxan lên bề mặt của nanosilica.…”
Section: Phổ Ft-ir Của Nanosilica Trước Và Sau Chức Hóaunclassified
“…The silica particles play a different role in each of the above applications. The quality of these products is highly dependent on the size and size distribution of the particles [24]. Stöber et al [25] reported in 1968 a pioneering method for the synthesis of spherical and monodisperse silica nanoparticles from aqueous alcohol solutions of silicon alkoxides in the presence of ammonia as a catalyst, and different sizes of silica nanoparticles ranging from 50 nm to 1 µm with a narrow size distribution were prepared.…”
Section: Introductionmentioning
confidence: 99%